Factors Influencing Brand Building and Brand Communication on Social Network of Meat Processing Products Cluster in Ubon Ratchathani - Suntramethakul, Anan; Poramatworachote, Pimvimol (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
This research aims to study factors influencing brand building and brand communication on social network of meat processing products cluster in Ubon Ratchathani. The sample is 400 customers who purchased products through social network in Ubon Ratchathni. Tool used in this research is 5-point scale questionnaire with reliability of .96. The statistics used in data analysis were frequency, mean, standard deviation and multiple regression analysis. The results showed that the influencing brand building and brand communication on social network of meat processing products cluster in Ubon Ratchathani consisted of 3 factors that were brand communication on social network, brand awareness and perception of quality. Moreover, coefficient of factors prediction for both values (R = 0.643) and independent variables could forecast dependent variables effectively (R2adj) for 40.90% with 0.01 level of significance.